Effect of potassium rates and application methods in no-till on soil K availability and crop yield - Gustavo Pesini; Dayana Jéssica Eckert; Matheus Ferrari Menegat; Gustavo Frosi; João Pedro Moro Flores; Lucas Aquino Alves; Dionata Filippi; Tadeu Luis Tiecher; Danilo Rheinheimer dos Santos; Tales Tiecher (Revista Brasileira de Ciência do Solo)
ABSTRACT The combination of potassium (K) fertilization with the adoption of no-tillage (NT) increases the concentration gradient of K in the soil, requiring subsurface layers to diagnose fertility. This study aimed to evaluate the effect of K rates applied in band or broadcast on the soil K availability and soybean and wheat yield. The study was established in 2019 on a Latossolo (Ferralsol) in the northwest of Rio Grande do Sul State, Brazil, under NT since 2002. Summer soybeans and winter wheat were cultivated from 2020 to 2022, and rates of K (0, 50, 100, 150, and 200 kg ha-1) were applied annually at soybean sowing. Each rate of K was applied in a band at the seeding row or broadcast on the soil surface. Grain yields and the available K content in the soil at different soil layers (0.00-0.05, 0.05-0.10, 0.10-0.15, and 0.15-0.20 m) were evaluated after the soybean harvest in 2020/2021. The K applied remained close to the application site, at the 0.10-0.15 m layer when applied in band and at the 0.00-0.05 m layer when deposited by broadcast. Band application of K can decrease the K gradient and increase soybean and wheat yield when the available K content is below 64 mg dm-3 in the 0.10-0.20 m soil layer, coinciding with the critical level adopted in the south of Brazil until 2016. The replacement of K removed by soybean and wheat grains under NT with low soil K availability at 0.10-0.20 m should be band applied in-furrow along the sowing line.